Mediation effect of cognitive impairment for the relationship of type 2 diabetes mellitus with mortality among elderly individuals - Wei, Boyang; He, Jun (Frontiers in Endocrinology, 2024)
Objectives: To investigate the potential mediating role of cognitive impairment on the link between type 2 diabetes mellitus (T2DM) and mortality among elderly individuals using data from the National Health and Nutrition Examination Survey (NHANES) database.Totally, 1,891 individuals from the NHANES database were included in this cohort study. All-cause mortality was considered study endpoint. Cognitive impairment was assessed by digit symbol substitution test (DSST). Adopted weighted logistic regression analyses to explore the relationship of T2DM with cognitive impairment.Constructed weighted Cox proportional hazard models to investigate the relationship of T2DM with all-cause mortality. We employed distribution-of-the-product method to investigate the mediating effect. RMediation software package was used to calculate the 95% confidence interval (CI) of the distribution-of-the-product. If CI does not contain 0, it suggests a significant mediation effect.The findings from the weighted logistic regression revealed that individuals with T2DM had a significantly higher likelihood of experiencing cognitive impairment [odds ratio =1.86, 95% CI: 1.39-2.49]. The result showed that T2DM was related to an increased all-cause mortality (hazard ratio=1.37, 95%CI: 1.01-1.87). Importantly, the mediation effect of cognitive impairment on the relationship of T2DM with all-cause mortality is significant (95%CI: 0.06-0.59). The percentage of mediation effect was calculated as 16.2%.Our study suggested that the presence of cognitive impairment plays a significant role in explaining the link between T2DM and all-cause mortality in older individuals.